2021
DOI: 10.1016/j.celrep.2021.109729
|View full text |Cite
|
Sign up to set email alerts
|

UQCRC1 engages cytochrome c for neuronal apoptotic cell death

Abstract: Highlights d Neuronal reduction of uqcrc1, the ETC complex III subunit, causes PD-like symptoms d uqcrc1 regulates DA neuronal maintenance and locomotor activity in flies d The disease-associated uqcrc1 variant fails to bind cytochrome c, triggering apoptosis d Targeting cytochrome c, but not ROS, ameliorates uqcrc1mediated neurodegeneration

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 46 publications
(58 reference statements)
0
12
0
Order By: Relevance
“…In Drosophila and mouse models, URCRC1 p.Y314S knock-in organisms showed dopaminergic neuronal loss, age-dependent locomotor deficits, and peripheral neuropathy [ 112 ]. Disruption of the Uqcrc1 gene in mice causes embryonic lethality [ 114 ], and deficiency of Uqcrc1 in Drosophila increases the cytochrome c in the cytoplasmic fraction and activates the caspase cascade, thus causing a reduction of dopaminergic neurons and neurodegeneration [ 115 ].…”
Section: Recently Described Parkinson’s Disease Genesmentioning
confidence: 99%
“…In Drosophila and mouse models, URCRC1 p.Y314S knock-in organisms showed dopaminergic neuronal loss, age-dependent locomotor deficits, and peripheral neuropathy [ 112 ]. Disruption of the Uqcrc1 gene in mice causes embryonic lethality [ 114 ], and deficiency of Uqcrc1 in Drosophila increases the cytochrome c in the cytoplasmic fraction and activates the caspase cascade, thus causing a reduction of dopaminergic neurons and neurodegeneration [ 115 ].…”
Section: Recently Described Parkinson’s Disease Genesmentioning
confidence: 99%
“…In line with these observations, and the fact that RTP801 induces neuron-death 1,4 , we found that EVs derived from neurons overexpressing RTP801 (RTP801-EVs) contained higher levels of pro-apoptotic proteins (such as cytochrome b-c1, cytochrome c and alpha-internexin) and lower levels of anti-apoptotic proteins (such as core histone macro-H2A, NDRG3 protein, and endophilin). When the apoptotic cascade is initiated, cytochrome c is released to the cytosol 67,143 . Other apoptotic-related proteins, such as alphainternexin 73,74 , phosducin-like protein 3 86 , neogenin 91,92 , and transmembrane protein 2 144 , might be activated also in response to RTP801 to accelerate the cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, ubiquinol‐cytochrome c reductase core protein 1 (UQCRC1), an evolutionarily conserved core subunit of mitochondrial respiratory chain complex III, was shown to prevent neuronal demise by engaging Cyt‐c, which is conserved in flies and humans (Hung et al. , 2021).…”
Section: Introductionmentioning
confidence: 99%